Let's solve each equation step by step.
-
For the equation \( 5x - 3 - x = 21 \):
Combine like terms: \[ 5x - x - 3 = 21 \] \[ 4x - 3 = 21 \] Add 3 to both sides: \[ 4x = 21 + 3 \] \[ 4x = 24 \] Divide by 4: \[ x = 6 \]
The answer is \( x = 6 \).
-
For the equation \( 7x - 3 - 4x = 9 \):
Combine like terms: \[ (7x - 4x) - 3 = 9 \] \[ 3x - 3 = 9 \] Add 3 to both sides: \[ 3x = 9 + 3 \] \[ 3x = 12 \] Divide by 3: \[ x = 4 \]
The answer is \( x = 4 \).
-
For the equation \( 6x - 8 = 2x + 4 \):
Move \( 2x \) to the left side: \[ 6x - 2x - 8 = 4 \] \[ 4x - 8 = 4 \] Add 8 to both sides: \[ 4x = 4 + 8 \] \[ 4x = 12 \] Divide by 4: \[ x = 3 \]
The answer is \( x = 3 \).
-
For the equation \( 5(-2x + 4) = 40 \):
Distribute the 5: \[ -10x + 20 = 40 \] Subtract 20 from both sides: \[ -10x = 40 - 20 \] \[ -10x = 20 \] Divide by -10: \[ x = -2 \]
The answer is \( x = -2 \).
Final answers are:
- \( x = 6 \)
- \( x = 4 \)
- \( x = 3 \)
- \( x = -2 \)